A porção superior da Formação Corumbataí (Permiano, Bacia do Paraná) na região de Piracicaba (SP) - Lopes, Fernando Danubio Sousa [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The present study describes and interprets the upper part of the Corumbataí Formation (Passa Dois Group, Paraná Basin, Permian, Kungurian-Roadian) and the basal part of the Piramboia Formation (São Bento Group, Jurassic?) in the northwest region of Piracicaba city (SP). A stretch of three kilometers of the highway SP-304, partially in duplication works, offered excellent expositions from the Condomínio Colinas de Piracicaba (UTM 7.491.618N/ 213.671E, datum Córrego Alegre) towards Águas de São Pedro. This study presents a detailed characterization of the sedimentary facies and of the boundary between the two formations; a preliminary identification of the main fossils; three columnar sections on a scale of 1:100, which were correlated for a composite columnar section of 48.5 m; collection, petrologic and petrographic analyses of samples and 16 thin sections; preliminary stratigraphic correlations with a previously described well between Botucatu and Anhembi; and the data interpretation focusing on the paleoenvironments, paleoclimates and cyclic successions. The predominant lithologies are heterolithic rocks (couplets of claystone/siltstone and very fine/fine sandstones) with flaser, wavy and lenticular bedding, frequently bioturbated and with mudcracks, organized in coarsening upwards cyclic successions, sometimes covered by fine sandstones with wave or hummocky cross stratification. Few calcilutite/biomicrite beds in a 1.5 m thick interval bear abundant fossils as ostracods, fish scales and teeth, coprolites, stem fragments and microphylls of lycophites and tiny pecopterids. The obtained data are coherent with previous interpretations for equivalent intervals of the Corumbataí Formation, i.e., the sedimentation probably occurred in an epeiric sea without evident communication with the open ocean, influenced by storm... (Complete abstract electronic access below)

O presente trabalho descreve e interpreta a parte superior da Formação Corumbataí (Grupo Passa Dois, Bacia do Paraná, Permiano, Kunguriano-Roadiano) e da parte basal Formação Piramboia (Grupo São Bento, Jurássico?) na região noroeste de Piracicaba (SP). Um trecho de aproximadamente três km da Rodovia SP-304, parcialmente em obras para duplicação, ofereceu excelentes exposições a partir do Condomínio Colinas de Piracicaba (UTM 7.491.618N/ 213.671E, datum Córrego Alegre) no sentido de Águas de São Pedro. O trabalho abrangeu a caracterização detalhada das fácies e do contato entre as duas formações; a identificação preliminar dos principais fósseis; a confecção de três seções colunares na escala 1:100, posteriormente correlacionadas para a construção de uma seção colunar composta de 48,5 m; a coleta, a preparação e o estudo de amostras, inclusive a análise petrográfica de 16 lâminas; a realização de correlações estratigráficas preliminares com um poço entre Botucatu e Anhembi; e a interpretação dos dados com ênfase na interpretação dos paleoambientes, paleoclimas e das sucessões cíclicas. As litologias predominantes são rochas heterolíticas de argilitos/siltitos alternados com arenitos muito finos a finos, frequentemente bioturbadas e com pequenas gretas de contração, organizados em sucessões cíclicas granocrescentes, podendo estar sobrepostos por arenitos finos com estratificação cruzada por ondas ou hummocky. Na área de estudo foi observado um intervalo com algumas camadas de calcilutitos (ou biomicritos na classificação petrográfica), onde se concentram abundantes fósseis como ostracodes, restos de peixes, coprólitos, fragmentos de caules e micrófilos de licófitas e minúsculas pecopterídeas. Os dados obtidos revelaram-se ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Geologia estratigráfica - Permiano; Diques (Geologia); Petrologia; Piracicaba (SP); Paraná, Bacia